THE IMPACT OF CITY FORMATION IN GREAT SELJUKS ON THE CITY CULTURE OF ANATOLIAN SELJUKS - Tülay METİN (Fırat University, 2019)
An urbanization oriented formation can be observed in the development and housing activities enhanced based on the socio-economic conditions parallel to a settling life during the foundation period of the Great Seljuk Empire. The urban culture which was formed based on the Sasanians, Islamic, Samanians, Ghaznavids and Karakhanids gained a new pace during the Seljuks period and came to the fore. Several other coeval or follower states of Seljuks dominated the Islamic world shortly, which were established in Persia, Anatolia, Iraq, Syria and Egypt, were carrying political, social and cultural traces of Seljuks. It is evident that among these states, the Seljuk of Anatolia which was established as a branch of the Great Seljuk Empire presented this impact more clearly. The Seljuk city establishment process in the Anatolia took place within the uncontrolled lands or in the lands captured from the Byzantines and it was structured with conscious development policy which is specific to Seljuks. Similar applications of Seljuks which carry a fallow-up characteristic of the ones formed systematically in the Persian territory regarding city and urbanization activities were continued in the Anatolia through addition of some advancement. Undoubtedly, a different territory and existence of a different prior formation were fused once more under the Seljuk impact. The effect of the urban culture existed within the Khorasan territory since the foundation of the Seljuks over the cities of Seljuks of Turkey is an outstanding subject that is needed to be investigated through comparison by taking institutions and other primary factors into account.